2012
DOI: 10.1093/infdis/jis650
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Memory T Cells and Naturally Acquired Antibodies in Plasmodium vivax Malaria-Exposed Individuals Against a Group of Tryptophan-Rich Antigens With Conserved Sequences

Abstract: These results suggest the presence of memory T cells in humans against these antigens to generate faster and more specific immune responses to minimize the P. vivax infection. Further characterization of these PvTRAgs may lead to the identification of a potential therapeutic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 41 publications
4
33
0
Order By: Relevance
“…However, it is difficult to verify whether anti-PvTRAg is stable in the P. vivax population based on incident measurement of antibody levels among different individuals. In the current study, we evaluated antibody responses against all PvTRAgs and found different sensitivities, whereas a previous report described a 75% to 100% seropositive rate (11). This may be due to the different origins of the serum samples, as we used samples from low-endemicity area, whereas the previous study used samples from areas of high endemicity, where reinfection was common (11).…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…However, it is difficult to verify whether anti-PvTRAg is stable in the P. vivax population based on incident measurement of antibody levels among different individuals. In the current study, we evaluated antibody responses against all PvTRAgs and found different sensitivities, whereas a previous report described a 75% to 100% seropositive rate (11). This may be due to the different origins of the serum samples, as we used samples from low-endemicity area, whereas the previous study used samples from areas of high endemicity, where reinfection was common (11).…”
Section: Discussionmentioning
confidence: 84%
“…These antibodies induced from malaria parasite infection were found to play important roles in several mechanisms, including inhibition of parasite invasion, blockage of parasite development, and enhancement of the phagocytic activity of monocytes and macrophages (26,27). In the current study, we analyzed IgG antibody responses against all of the PvTRAg family proteins in a larger number of serum samples from vivax malaria patients and malaria-naive individuals than in previous PvTRAg studies (11,16). Nine novel TRAg proteins (PvTRAg_3, PvTRAg_7, PvTRAg_13, PvTRAg_14, PvTRAg_15, PvTRAg_18, PvTRAg_20, PvTRAg_26, and PvTRAg_35) showed higher IgG positivity (Ն51.8%) in patients' sera.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations